Meningkatkan Daya Saing Produk Usaha Rumahan Keripik Singkong di Bandar Setia Kecamatan Percut Sei Tuan Kabupaten Deli Serdang: Sejarah Home Industri Keripik Singkong - Siti Asiah; Zainarti Zainarti; Anni Zuhro Syafrida Hasibuan; Anjali Marwiyah Siregar; Sallimah Ika Putri Malau (STIT Sirojul Falah Bogor, 2023)
Grandma Parinem, who runs a small home business making cassava chips, is the partner in this community service project. The partners' cassava chips are deliciously flavorful, but sadly, this industry is still in its infancy and appears staid. which uses conventional tools and a very straightforward production process to create the snack food cassava chips in the Bandar Setia Hamlet. Although this enterprise does not yet have a business license and is not yet halal labeled, the creation of the cassava chips in Hamlet IV, Bandar Setia, Kec. Percut Sei Tuan, Kab. Deli Serdang, North Sumatra does not break Islamic sharia laws because no haram components are mixed in. Additionally, the researcher saw that the production already followed Islamic law. The people of Bandar Setia Hamlet's economy have benefited from this cassava chip company. In general, the manufacturing mechanisms comprise machinery, structures, production management, the method of making cassava chips, and cassava chip marketing. High consumer demand, which makes it simple to sell the products of this domestic sector, and a strong desire to grow this cassava chip business in order to boost the local economy are the factors that encourage the development of this business. While there is fierce rivalry in the chip industry, the product doesn't last very long, and the weather can vary, making it impossible to market cassava chips when it rains because there aren't many places to sell them.